Who and what should we educate our students to be?An inquiry into the cultivation of multiculturalism in education - WEI, LIPING (Journal of Education Culture and Society, 2020)
A young Chinese immigrant’s aversion to his Chinese origin and his self-identifi cation as purely American gives much food for thought to the author: Whoand what American edu-cation has been aiming to educate its students to be and what is impeding multiculturalism from being cultivated in education. The article points out that American schools have long been serving to Americanize its immigrant population regardless of where they are originally from, ethnically, linguistically, culturally, and religiously, and in spite of the country’s long--standing and ever-growing diversity. Without challenging the structural inequality inherent in “assimilation”, true multiculturalism will not be realized in education.